2015
DOI: 10.1007/s11232-015-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation time of quark–gluon plasma in heavy-ion collisions in the holographic shock wave model

Abstract: Abstract:We estimate the thermalization time in two colliding shock waves holographic model of heavy-ion collisions. For this purpose we model the process by the Vaidya metric with a horizon defined by the trapped surface location. We consider two bottom-up AdS/QCD models that give, within the colliding shock waves approach, the dependence of multiplicity on the energy compatible with RHIC and LHC results. One model is a bottom-up AdS/QCD confining model and the other is related to an anisotropic thermalizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…We see that the thermalization time behaves linearly with . The results match to those for modified AdS models from [34] and coincide for all values of the dynamical exponent ν.…”
Section: Jhep09(2016)142supporting
confidence: 76%
See 1 more Smart Citation
“…We see that the thermalization time behaves linearly with . The results match to those for modified AdS models from [34] and coincide for all values of the dynamical exponent ν.…”
Section: Jhep09(2016)142supporting
confidence: 76%
“…Further, we construct a Vaidya-type geometry asymptoting to the Lifshitz-like solution to model a gravitation collapse in order to study the holographic thermalization. The Vaidya metric with Lifshitz scaling was used for the examination of the holographic thermalization in [33,34]. There, it has been shown that for the metric…”
Section: Jhep09(2016)142mentioning
confidence: 99%
“…It is called the holographic entanglement entropy (HEE) and is defined as the area of a minimal surface extending from some predefined surface A on the boundary into the bulk [27][28][29]. The HEE during thermalization usually evolves to the thermal entanglement entropy [30][31][32][33][34][35][36][37][38]. With this approach, there is a natural possibility of studying the evolution of entropy in HIC (thermalization) and phase transitions for the obtained thermal media in the framework of the same holographic model.…”
mentioning
confidence: 99%
“…It is called the holographic entanglement entropy (HEE) and is defined as the area of a minimal surface extending JHEP07(2020)043 from some predefined surface A on the boundary into the bulk [28][29][30]. The HEE during thermalization usually evolves to the thermal entanglement entropy [31][32][33][34][35][36][37][38][39][40][41][42]. With this approach, there is a natural possibility of studying the evolution of entropy in HIC (thermalization) and phase transitions for the obtained thermal media in the framework of the same holographic model.…”
Section: Jhep07(2020)043mentioning
confidence: 99%
“…Figure34. Top line: vs z * for F=EF for ϕ = 0 (longitudinal case) at (a) z h = 1.2, 1.138, 1.108, 1 and µ = 0, at (b) z h = 2, 2.5, 3.0, 3.5 and µ = 0.5.…”
mentioning
confidence: 99%